Genetic polymorphism in the serotonin transporter gene-linked polymorphic region and response to serotonin reuptake inhibitors in patients with premature ejaculation - Ozbek, Emin (Clinics (Sao Paulo), 2014)
OBJECTIVES: Serotonin plays a central role in ejaculation and selective serotonin reuptake inhibitors have been successfully used to treat premature ejaculation. Here, we evaluated the relationship between a polymorphism in the serotonin transporter gene-linked polymorphic region (5-HTTLPR) and the response of patients with premature ejaculation to SSRI medication. METHODS: Sixty-nine premature ejaculation patients were treated with 20 mg/d paroxetine for three months. The Intravaginal Ejaculatory Latency Time and International Index of Erectile Function scores were compared with baseline values. The patients were scored as having responded to therapy when a 2-fold or greater increase was observed in Intravaginal Ejaculatory Latency Time compared with baseline values after three months. Three genotypes of 5-HTTLPR were studied: LL, LS and SS. The appropriateness of the allele frequencies in 5-HTTLPR were analyzed according to Hardy-Weinberg equilibrium using the χ(2)-test. RESULTS: The short (S) allele of 5-HTTLPR was significantly more frequent in responders than in nonresponders (p<0.05). Out of the 69 total PE patients, 41 patients (59%) responded to therapy. There was no significant difference in the International Index of Erectile Function score at the end of therapy between the responder and nonresponder groups. The frequencies of the L allele and S allele were 20% and 39%, respectively, in the responder group (p<0.05). CONCLUSION: We conclude that premature ejaculation patients with the SS genotype respond well to selective serotonin reuptake inhibitor therapy. Further studies with large patient groups are necessary to confirm this conclusion.